KONSEP KOTA CERDAS SEBAGAI ALTERNATIF PENYELESAIAN MASALAH PERKOTAAN DI SURABAYA - Kurniawati, Risa Amalia; Purnomo, Nugroho Hari (Universitas Syiah Kuala, 2023)
Globalization has a great impact on people's lives. One of them is the increasing pressure and need for government services to achieve alternative solutions to urban problems. This study aims at the problems of smart people as an indicator of the success of a smart city in Surabaya. Smart people are one of the supporting dimensions of the realization of a smart city. This study uses a qualitative descriptive analysis method by observing and analyzing the actions of the Surabaya City government in implementing a smart city. So that the factors that make a city smart, one of which is measured by the quality of its human resources; which includes the human development index which is measured by how the unemployment rate, poverty level, and health problems, and also seen from the aspect of community knowledge in receiving information, disseminating information, related to the growth of creativity carried out and also the inclusiveness of empowering activities carried out by several people. In addition, the activities found in the city of Surabaya in its community activities already have quite innovative and creative networks.